Dynamics of Monetary Freedom, Labour, and FDI in Indonesia: A VECM Analysis - Komarlina, Dwi Hastuti Lestari; Susilo, Ignatia Bintang Filia Dei; Ramadhan, Rifky Wahyu; Hamzah, Risna Amalia; Bayanudin, Rahma Putri; Fatin, Sausan (Universitas Negeri Semarang, 2025)
The research outlined here was directed by the Vector Error Correction Model (VECM) in its investigation of the connection between monetary freedom, labor market, and foreign direct investment in Indonesia. Historical time series data have been used in the model and diagnostic tests employed to ensure the validity and reliability of the results. The cointegration test confirms the cointegration of all variables which reflects the presence of linkages both in the short run and long run. This research contributes to the understanding of monetary freedom, labor market dynamics, and foreign direct investment in Indonesia through a better comprehension of their economic interrelationships.